Réponses

2014-10-10T20:57:31+02:00


C = - 2 (- 2x + 7) - (- x + 2) (- x + 2) (5 - 4x)

C = 4x - 14 - ( x² - 2x - 2x + 4) ( 5 - 4x)

C = 4x - 14 - ( x² - 4x + 4) (5 - 4x)

C = 4x - 14 - ( 5x² - 4x³ - 20x + 16x² + 20 - 16x)

C = 4x - 14 - 5x² + 4x³ + 20x - 16x² - 20 + 16x

C = 4x³ - 21x² + 40x - 34



-2 (3x + 5) = 7 + x

-6x - 10 = 7 + x

-6x - 10 + 10 = 7 + x + 10

-6x = x + 17

-6x - x = x + 17 - x

-5x = 17 

x = 3,4

Meilleure réponse !
2014-10-10T21:13:39+02:00
Développer et réduire l'expression :
C = - 2 (- 2x + 7) - (- x + 2) (- x + 2) (5 - 4x)
C = 4x - 14 - ( x² - 2x - 2x + 4) ( 5 - 4x)
C = 4x - 14 - (5x² - 4x³ - 10x + 8x²  - 10x + 8x² + 20 - 16x)
C = 4x - 14 - ( 5x² - 4x³ - 20x + 16x² + 20 - 16x)
C = 4x - 14 - 5x² + 4x³ + 20x - 16x² - 20 + 16x
C = 4x³ - 21x² + 40x - 34

Résoudre l'équation :
- 2 (3x + 5) = 7 + x
- 6x - 10 = 7 + x
- 6x - x = 7 + 10
- 7x = 17
x = - 17/7